The Relationship Between Workload And The Incidence Of Musculoskeletal Disorders In Textile Industry Workers In West Java - Prasetyo, Budi (Journal of International Public Health, 2023)
Musculoskeletal disorders are occupational diseases that are often suffered by workers. Symptoms can include pain, swelling and even numbness. Cardiopulmonary endurance also plays an important role in the occurrence of musculoskeletal disorders. The heavier a job, the more oxygen the body needs to oxidize and the more blood flow carries oxygen. In people with heavy workloads, the heart's pumping activity changes, so that when the person works, oxygen transport to the muscles is disrupted. Objectives: The purpose of this study was to determine the relationship between workload and musculoskeletal complaints in workers at PT. Kerta Rajasa Raya Sidoarjo. Design: The research design used a cross-sectional approach. The number of samples obtained was 43 respondents in 2 work divisions, namely the extruder division and ABM. Respondents' workload was measured based on cardiovascular load (CVL) and musculoskeletal complaints were measured using the Nordic Body Map (NBM). Results: The results of the Pearson correlation test, obtained a p value = 0.002 where p <0.05. From the results of the statistical test, it was stated that there is a positive relationship between workload and musculoskeletal complaints. Conclusions: Based on the results of the study, it is recommended that companies reduce the workload so that it can reduce the occurrence of musculoskeletal disorders.